Indicators and medical tests to identify lower limb swelling causes after total knee arthroplasty: a Delphi study with multidisciplinary experts - Lin Yang; Bei-Ying Wu; Cai-feng Wang; Hui-Wu Li; Wei-Wei Bian; Hong Ruan (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Lower limb swelling after total knee arthroplasty (TKA) hinders surgical effectiveness. The poor results of studies on swelling interventions are due to the lack of a classification of swelling causes through appropriate medical tests. A gold standard is missing. This study aimed to clarify the causes of TKA postoperative swelling and how to identify them through indicators and medical tests by consulting a wide range of experts from multiple disciplines. Method The Delphi method was used. A first draft of the index was prepared based on a systematic search of the literature. A total of 11 experts from several disciplines were invited to evaluate the rationality of the indicators and suggest modifications. After two rounds of consultation, the experts reached a consensus, and the consultation was stopped. Results The response rate of the 11 experts was 100%, and the authoritative Cr was 0.896. Kendall's W values for opinion coordination of the two rounds of consultation were 0.262 and 0.226, respectively (P < 0.001). Among the final indicators, there were 4 primary indicators for swelling cause classification (inflammatory response, poor venous return, joint hematoma, muscle damage, and healing), 19 secondary and 19 tertiary indicators. Conclusion The indications obtained by systematic literature review and multidisciplinary expert consultation are reliable and scientific. Multiple causes of lower extremity swelling after TKA were identified. Blood test indicators can reflect an inflammatory response, suggest poor venous return, and reflect muscle damage and healing progress. Ultrasound scans are needed to identify underlying thrombotic or valvular problems, joint hematomas, and muscle damage. These tests help clinicians and researchers determine the cause of swelling after TKA and take appropriate management.